The macroeconomic effects of exchange rate movements - Pablo Anaya; Stefan Hasenclever (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
The macroeconomic effects of exchange rate movements have been subject to an extensive debate in international economics. Traditionally, much of the discussion was focused on the relation between the effective exchange rate and the trade balance. However, the process of financial globalization has led to a sharp increase in foreign asset and liability positions across countries and also to a greater dispersion in foreign currency positions, with many countries being either large net creditors or net debtors in foreign currency. This has shifted the focus of the discussion from the trade balance to the external balance sheets of countries. This Roundup provides a brief overview of the literature on the macroeconomic impact of exchange rate movements.
Keywords: 330